High-voltage ceramic capacitor dielectric material, high-voltage ceramic capacitor and preparation method
Patent Information
- Application Number
- CN202611245112.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明实施例提供一种高压陶瓷电容器介质材料、高压陶瓷电容器及制备方法,旨在解决现有技术中高压陶瓷电容器介质材料存在的介电常数范围窄、介质损耗偏高、宽温容量稳定性和高压电气可靠性差及含铅不环保等缺陷
[0026]本发明实施例提供的高压陶瓷电容器介质材料、高压陶瓷电容器及制备方法,采用钡钛主相加上三元稀土、铋、铌、锆酸钙,通过调整原料配比达到了120~180的较宽介电常数范围,增加了配方兼容性,可以满足不同场合的应用需求;采用多种稀土搭配锆酸钙稳定晶格,配合精细研磨、长时间均匀烧结,减少了温度带来的容量突变,在覆盖-40℃低温至70℃高温的户外工作温度中温度稳定性好,户外四季温差下分压稳定,计量误差小;该介质材料中采用铌元素填补晶格空位降低损耗,采用铋元素再搭配长时烧结让瓷体致密无气孔,稀土强化晶界绝缘,使得高压工作发热少,介质损耗低,局放性能好,延长了产品使用寿命长;采用氧化铋、锆酸钙替代传统铅组分提升耐压,全程不含铅原料,符合环保标准,同时解决普通无铅陶瓷耐压不足的问题,适配电网绿色设备要求。
Smart Images

Figure CN123003282A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic ceramic materials technology, specifically to a high-voltage ceramic capacitor dielectric material, a high-voltage ceramic capacitor, and a preparation method thereof. Background Technology
[0002] Currently, the mainstream power supply method for China's smart grid is passive voltage division, with high-voltage ceramic capacitors as the core component. Therefore, the performance indicators of these high-voltage ceramic capacitors directly determine the metering accuracy and outdoor lifespan of the entire system. The main performance indicators of high-voltage ceramic capacitors include dielectric constant, wide-temperature capacitance stability, dielectric loss, high-voltage electrical reliability, and lead-free environmental friendliness.
[0003] Currently, traditional commercial barium titanate high-voltage ceramics generally suffer from defects such as low dielectric constant, large capacity drift over a wide temperature range, poor high-voltage partial discharge performance, and lead content which is not environmentally friendly. Conventional single rare-earth-doped barium titanate ceramics have a dielectric constant of only 80~120, which cannot meet the requirements of the next generation of miniaturized high-capacity power-harvesting chips. On the other hand, the existing high-temperature stable NPO ceramic dielectric material (patent publication number: CN121583773A) has a dielectric upper limit of only 138, which is difficult to cover the high dielectric range of 120~180, and there is a significant performance gap.
[0004] In summary, the existing high-voltage ceramic capacitor dielectric materials generally have the following defects: (1) Narrow dielectric constant range, requiring the development of different formulation systems under different requirements, resulting in low formulation compatibility and greatly increasing R&D costs; (2) High dielectric loss, poor partial discharge performance, easy aging in high-temperature environments, shortening product lifespan; (3) Severe wide-temperature capacity drift, narrow temperature range, large capacity change rate at high or low temperatures, directly affecting the metering accuracy of power-taking devices; (4) Many grain boundary defects, accelerated capacity decay under long-term outdoor high and low temperature cycles and humid and hot environments, and irreversible capacity shift due to lightning strikes; (5) Due to the low withstand voltage level of lead-free products, many formulation systems often contain lead in order to improve withstand voltage performance, which is not suitable for social needs.
[0005] Therefore, there is an urgent need for a high-voltage ceramic capacitor dielectric material with a wide dielectric constant range, low dielectric loss, wide temperature stability, and lead-free and environmentally friendly properties. Summary of the Invention
[0006] This invention provides a high-voltage ceramic capacitor dielectric material, a high-voltage ceramic capacitor, and a preparation method thereof, aiming to solve the defects of existing high-voltage ceramic capacitor dielectric materials, such as narrow dielectric constant range, high dielectric loss, poor wide-temperature capacitance stability and high-voltage electrical reliability, and lead content which is not environmentally friendly.
[0007] In a first aspect, embodiments of the present invention provide a high-voltage ceramic capacitor dielectric material, said material being made from the following raw materials by weight percentage:
[0008] Barium carbonate 40%~45%, titanium dioxide 35%~40%, dysprosium trioxide 1.2%~3.0%, gadolinium trioxide 1.0%~2.8%, samarium trioxide 2.0%~4.2%, bismuth trioxide 3.5%~7.0%, niobium pentoxide 0.8%~2.2%, calcium zirconate 2.5%~5.5%.
[0009] Secondly, embodiments of the present invention provide a method for preparing a high-voltage ceramic capacitor, comprising the following steps:
[0010] Barium carbonate, titanium dioxide, dysprosium trioxide, gadolinium trioxide, samarium trioxide, bismuth trioxide, niobium pentoxide, and calcium zirconate were mixed uniformly in a weight percentage ratio of 40%~45%: 35%~40%: 1.2%~3.0%: 1.0%~2.8%: 2.0%~4.2%: 3.5%~7.0%: 0.8%~2.2%: 2.5%~5.5% to obtain a mixed raw material. The mixed raw material was then added to grinding media, dispersion media, and dispersion aids and subjected to wet ball milling. After sieving, a primary slurry was obtained. The primary slurry was then subjected to sand milling dispersion treatment to obtain a uniform media slurry.
[0011] The medium slurry is centrifuged and sprayed to obtain granulated particles; the granulated particles are sieved, and powder within the target particle size range is added to the powder, followed by mixing and homogenization to obtain the mixed granulated material.
[0012] The granulated material is pressed into shape to obtain a blank of the target density;
[0013] The blank is subjected to a pre-firing process to remove the glue, resulting in a pre-firing blank with the glue removed.
[0014] The debonded green body is subjected to high-temperature sintering treatment to obtain a sintered ceramic body;
[0015] The sintered ceramic body is post-processed and the electrodes are encapsulated to produce a high-voltage ceramic capacitor.
[0016] In a preferred embodiment of the present invention, in the step of obtaining the primary slurry after sieving, the grinding medium is zirconium balls, the dispersion medium is deionized water, and the dispersion aid includes a binder, a dispersant, and a defoamer.
[0017] The mass ratio of the mixed raw materials, the grinding media, the dispersing media, the binder, the dispersant and the defoamer is 1:3:1:0.1:0.01:0.01.
[0018] In a preferred embodiment of the present invention, in the step of obtaining a uniform media slurry, the rotation speed of the sand mill dispersion treatment is 2100~2500 r / min, and the number of cycles is 15~25.
[0019] As a preferred embodiment of the present invention, in the step of obtaining granulated particles, the process parameters of the centrifugal spray granulation are: inlet temperature of 230℃~250℃, outlet temperature of 100℃~120℃, and atomizer frequency of 120Hz~150Hz.
[0020] In a preferred embodiment of the present invention, in the step of obtaining the mixed granulated material, the target particle size range is 80 mesh to 250 mesh;
[0021] In the step of obtaining the mixed granulated material, the release agent is calcium stearate, and its addition amount is 0.1% to 0.4% of the powder mass; the mixing and homogenization treatment time is 40 min to 1 h.
[0022] In a preferred embodiment of the present invention, in the step of obtaining the blank with the target density, the target density of the blank is 3.7 g / cm³ to 3.8 g / cm³.
[0023] In a preferred embodiment of the present invention, in the step of obtaining the degummed blank, the temperature of the degummed preheating treatment is 600℃~700℃, and the holding time is 5h~10h.
[0024] In a preferred embodiment of the present invention, in the step of obtaining the sintered ceramic body, the temperature of the high-temperature sintering treatment is 1280℃~1380℃, the total firing time is 25h~30h, and the holding time is 3h~5h.
[0025] Thirdly, embodiments of the present invention provide a high-voltage ceramic capacitor, which is prepared by the high-voltage ceramic capacitor preparation method as described in the second aspect and its preferred embodiments.
[0026] The high-voltage ceramic capacitor dielectric material, high-voltage ceramic capacitor, and preparation method provided in this invention adopt a barium-titanium main phase with ternary rare earth elements, bismuth, niobium, and calcium zirconate. By adjusting the raw material ratio, a wide dielectric constant range of 120~180 is achieved, increasing formula compatibility and meeting the application requirements of different occasions. The use of multiple rare earth elements combined with calcium zirconate stabilizes the crystal lattice. Combined with fine grinding and long-term uniform sintering, it reduces the capacitance mutation caused by temperature. It has good temperature stability in outdoor working temperatures ranging from -40℃ to 70℃, and stable voltage division under outdoor seasonal temperature differences with small measurement errors. In this dielectric material, niobium is used to fill lattice vacancies to reduce losses, and bismuth is used in combination with long-term sintering to make the ceramic body dense and pore-free. Rare earth elements strengthen grain boundary insulation, resulting in less heat generation during high-voltage operation, low dielectric loss, good partial discharge performance, and extended product life. The use of bismuth oxide and calcium zirconate to replace traditional lead components improves the withstand voltage. The entire process is lead-free, meeting environmental protection standards, and solving the problem of insufficient withstand voltage of ordinary lead-free ceramics, making it suitable for the requirements of green power grid equipment.
[0027] Furthermore, the preparation method employs ball milling and high-speed sand milling to refine the powder, while segmented debinding, long-term sintering to eliminate internal stress in pores, and calcium zirconate to strengthen grain boundaries. This results in slow capacity decay under long-term outdoor temperature differences and humidity, and the capacity will not permanently shift after a lightning strike. The equipment has a longer maintenance-free period, reducing operation and maintenance costs. By using fixed process parameters for ball milling, sand milling, granulation, and sintering, and by standardizing the sieving particle size and adding a release agent, the performance differences between the same batch and different batches of products can be minimized, resulting in a high yield rate. Existing production lines can be put into production directly with low modification costs. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 This is a schematic flowchart illustrating a high-voltage ceramic capacitor and its preparation method according to an embodiment of the present invention.
[0030] Figure 2 This is a graph showing the rate of change of capacitance of the high-voltage ceramic capacitors prepared in Examples 1 and 2 of the present invention as a function of temperature. Detailed Implementation
[0031] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0032] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0033] Currently, the main performance indicators for evaluating high-voltage ceramic capacitors include: (1) Dielectric constant: The higher the dielectric constant, the larger the capacitance under the same volume, which can reduce the size of the capacitor chip and realize the miniaturization of the power extraction device; (2) Wide temperature capacitance stability: The outdoor working temperature covers low temperature of -40℃ to high temperature of 70℃. The smaller the change in capacitance with temperature, the more stable the voltage division ratio and the smaller the measurement error; (3) Dielectric loss: The lower the loss, the less heat is generated under high voltage, avoiding accelerated aging at high temperature; (4) High voltage electrical reliability: Including partial discharge initiation voltage, lightning impulse resistance, cold and hot cycle stability, and damp heat aging life; (5) Lead-free and environmentally friendly: Traditional systems contain a lot of lead in order to improve the withstand voltage performance, which is no longer suitable for social needs.
[0034] However, the performance of existing high-voltage ceramic capacitor dielectric materials cannot fully meet the above requirements and thus cannot satisfy the application needs. This invention effectively solves this technical problem by providing a high-voltage ceramic capacitor dielectric material with a wide dielectric constant range, low dielectric loss, wide temperature stability, and lead-free environmental friendliness, as well as a corresponding high-voltage ceramic capacitor manufacturing method.
[0035] This invention discloses a high-voltage ceramic capacitor dielectric material, which is made from the following raw materials by weight percentage:
[0036] Barium carbonate 40%~45%, titanium dioxide 35%~40%, dysprosium trioxide 1.2%~3.0%, gadolinium trioxide 1.0%~2.8%, samarium trioxide 2.0%~4.2%, bismuth trioxide 3.5%~7.0%, niobium pentoxide 0.8%~2.2%, calcium zirconate 2.5%~5.5%.
[0037] The high-voltage ceramic capacitor dielectric material provided in this embodiment exhibits synergistic interactions among its components, resulting in a dielectric constant of 120-180, low dielectric loss, and good partial discharge performance. Furthermore, it demonstrates excellent temperature stability under outdoor operating temperatures ranging from -40℃ to 70℃. Additionally, it is lead-free, environmentally friendly, and boasts a high withstand voltage.
[0038] Specifically, barium carbonate is one of the main materials used in the solid-state preparation of high-voltage ceramic capacitor dielectric materials. Its calcination and decomposition releases carbon dioxide gas, providing barium ions (Ba²⁺) which participate in the formation of a perovskite crystal structure. The barium ions (Ba²⁺) occupy the A-sites in the perovskite crystal structure, forming its fundamental structure.
[0039] Titanium dioxide is also one of the main materials for preparing high-voltage ceramic capacitor dielectric materials by solid-state methods, providing titanium ions (Ti). 4 ⁺, which occupies the B site in the perovskite crystal structure. The spontaneous polarization generated by the displacement of titanium ions within the oxygen octahedron is the fundamental source of the high dielectric constant of ceramics. When controlling the Ba / Ti ratio, a moderate excess of titanium is beneficial for suppressing grain coarsening, optimizing grain boundary insulation properties, and adapting to high-voltage operating conditions.
[0040] Dysprosium trioxide provides dysprosium ions (Dy³⁺), which replace barium ions at the A-site with different valences, making it a rare-earth dopant. Introducing dysprosium ions into the raw material can broaden the Curie phase transition peak, suppress the sharp drop in dielectric constant in the high-temperature range, and improve high-temperature capacitance stability; it can also refine the grains, optimize the microstructure, and improve the ceramic breakdown field strength; furthermore, it can construct defect dipoles, reduce capacitance decay under DC bias, and is suitable for long-term high-voltage operation, making it ideal for compensating for temperature drift in the high-temperature range.
[0041] Gadolinium trioxide provides gadolinium ions (Gd³⁺), which replace barium ions at the A-site with different valences. Also a rare-earth dopant, it induces lattice distortion through charge balance. Introducing dysprosium ions into the raw material can mitigate the decreasing trend of dielectric constant in the low-temperature range, improving low-temperature characteristics; it can also modulate grain boundary impedance, reduce leakage current, and improve insulation reliability under high voltage. Gadolinium trioxide and dysprosium trioxide can complement each other; dysprosium focuses on high temperatures, while gadolinium focuses on low temperatures, and their combination can broaden the stable temperature range.
[0042] Samarium trioxide provides samarium ions (Sm³⁺), which have a moderate radius and can be selectively doped at the A-site, and are also rare-earth dopants. Introducing samarium ions into the raw material can significantly broaden the Curie peak and greatly reduce the capacitance change rate across the entire temperature range; it can also suppress the ceramic aging effect and reduce dielectric loss; and it can also improve the ceramic's resistance to pulsed electric fields, making it suitable for long-term cyclic operation of high-voltage capacitors.
[0043] Bismuth trioxide is a liquid-phase sintering aid. It generates a liquid phase in the sintering zone, which promotes particle rearrangement, increases the density of the ceramic body, lowers the firing temperature, and reduces porosity. Porosity is the main cause of partial discharge under high voltage.
[0044] Niobium pentoxide provides niobium ions (Nb). 5Niobium ions (⁺) are typical B-site donor dopant ions that replace titanium ions in the crystal lattice. Introducing niobium ions into the raw material can promote the formation of a shell-core structure, achieving temperature flattening of the dielectric constant; it can also suppress abnormal grain growth, resulting in a uniform fine-grained structure, which can significantly improve the breakdown voltage and suppress electrical fatigue; it can also optimize grain boundary insulation properties and reduce the probability of partial discharge under pulsed voltage.
[0045] Calcium zirconate itself is a perovskite material with low dielectric properties and high temperature stability. It is not primarily ion-doped but exists mainly as an intergranular composite phase. It can disperse at the grain boundaries of barium titanate, alleviating lattice thermal stress caused by temperature changes, inhibiting the initiation of microcracks under thermal cycling, and improving the temperature cycling reliability of products. It can also further flatten the dielectric constant temperature curve and suppress the dielectric peak near the Curie temperature. Furthermore, it can form a synergy with rare earth doped systems, where rare earths regulate the internal polarization of the lattice, and calcium zirconate stabilizes the grain boundaries, jointly reducing high and low temperature capacity fluctuations. It can also improve the ceramic's resistance to electrical aging.
[0046] This dielectric material uses a barium-titanium main phase combined with ternary rare earth elements, bismuth, niobium, and calcium zirconate. By adjusting the raw material ratio, a wide dielectric constant range of 120~180 is achieved. A single basic formula can be used to manufacture capacitors of different specifications, eliminating the need to develop multiple separate systems. This increases formula compatibility, reduces R&D and production investment, and allows for smaller capacitor sizes and easier equipment miniaturization, meeting the application needs of various occasions.
[0047] Meanwhile, the dielectric material uses a combination of various rare earth elements with calcium zirconate to stabilize the lattice, and with fine grinding and long-term uniform sintering processes, it reduces the capacity mutation caused by temperature. It has good stability in outdoor working temperatures ranging from -40℃ to 70℃, and the capacity change rate is controlled within 0.2% across the entire temperature range. The partial pressure is stable under outdoor seasonal temperature differences, with small measurement error, and no additional temperature compensation accessories are required.
[0048] The dielectric material also uses niobium to fill lattice vacancies and reduce losses, and bismuth is used in combination with a long-time sintering process to make the ceramic body dense and free of pores. Rare earth elements strengthen the grain boundary insulation. The final product has no partial discharge at voltages above 33kV, no breakdown at 90kV withstand voltage, and passes all 110kV lightning impulse tests. It generates less heat during high-voltage operation, has low dielectric loss, good partial discharge performance, and extends the product's service life.
[0049] Finally, the dielectric material uses bismuth oxide and calcium zirconate to replace the traditional lead components to improve the withstand voltage. It contains no lead-free raw materials throughout the process, meets environmental protection standards, and solves the problem of insufficient withstand voltage of ordinary lead-free ceramics, making it suitable for the requirements of green power grid equipment.
[0050] In summary, through the synergistic effect of multiple modified components, this embodiment ultimately obtains a high-voltage ceramic capacitor dielectric material with a dielectric constant of 120-180, a small capacitance change rate over a wide temperature range, high breakdown field strength, suitable for high-voltage precision power extraction scenarios, and is lead-free.
[0051] Based on the above embodiments, referring to Figure 1 As shown in the figure, this invention also provides a method for preparing a high-voltage ceramic capacitor, which includes the following steps:
[0052] Step 101: Mix barium carbonate, titanium dioxide, dysprosium trioxide, gadolinium trioxide, samarium trioxide, bismuth trioxide, niobium pentoxide, and calcium zirconate in a weight percentage ratio of 40%~45%: 35%~40%: 1.2%~3.0%: 1.0%~2.8%: 2.0%~4.2%: 3.5%~7.0%: 0.8%~2.2%: 2.5%~5.5% to obtain a mixed raw material; add grinding media, dispersion media, and dispersion aid to the mixed raw material and perform wet ball milling; after sieving, obtain a primary slurry; perform sand milling dispersion treatment on the primary slurry to obtain a uniform media slurry.
[0053] In this step, barium carbonate, titanium dioxide, dysprosium trioxide, gadolinium trioxide, samarium trioxide, bismuth trioxide, niobium pentoxide, and calcium zirconate are prepared according to a preset weight percentage and then mixed evenly to obtain a mixed raw material.
[0054] Then, the above-mentioned mixed raw materials are placed in a ball mill, and grinding media, dispersion media and dispersion aids are added. After wet ball milling for 1 hour, the primary slurry is separated by passing it through a 200-mesh sieve.
[0055] In this embodiment, the grinding media is preferably zirconium balls, the dispersion media is preferably deionized water, and the dispersing aids include binders, dispersants, and defoamers. The mass ratio of the mixed raw materials, grinding media, dispersion media, binders, dispersants, and defoamers is 1:3:1:0.1:0.01:0.01. Repeated experiments have shown that adding too much grinding media and dispersion media to the mixed raw materials will affect the performance of the final product, while adding too little will affect product molding. At this ratio, the added grinding media, dispersion media, binders, dispersants, and defoamers do not affect the performance of the final product or its molding, representing the optimal ratio.
[0056] Finally, the above primary slurry is poured into a sand mill for sand milling and dispersion treatment to obtain a uniform media slurry.
[0057] In this embodiment, the preferred milling speed for dispersion is 2100~2500 r / min. Through repeated experiments, it was found that when the speed is less than 2100 r / min, the zirconium balls will enter the slurry, and the milling time will be relatively long; while when the speed is greater than 2500 r / min, the temperature of the slurry rises, leading to a hydrolysis reaction. A milling speed of 2100 r / min yields the best results for dispersion.
[0058] The optimal number of cycles is 15-25. Through repeated testing, it was found that if the number of cycles is less than 15, the particle size of the slurry is too coarse and cannot meet the particle size requirements; if the number of cycles is greater than 25, it will cause wear on the zirconium balls, and the impurities generated after wear will be carried into the slurry. The best results are achieved with 20 cycles.
[0059] Step 102: Centrifuge the slurry into granules to obtain granulated particles; sieve the granulated particles, take the powder within the target particle size range, add the release agent, and perform mixing and homogenization treatment to obtain the mixed granulated material.
[0060] In this step, the medium slurry obtained in the above steps is placed in a centrifugal granulation tower for centrifugal spray granulation to obtain granulated particles.
[0061] In this embodiment, during the centrifugal spray granulation process, the inlet temperature is preferably 230℃~250℃, and the outlet temperature is preferably 100℃~120℃.
[0062] The inlet temperature within this range falls into the medium-high temperature range, ensuring instantaneous flash drying of moisture while preventing excessively high temperatures from causing premature coking, carbonization, or loss of binding activity of the binder within the granulation tower. This ensures that the granulated particles possess sufficient green strength during subsequent tableting. The outlet temperature is controlled at 100℃~120℃, indicating sufficient heat exchange between the hot air and the droplets within the tower. This ensures that the final moisture content of the powder meets the standard while avoiding heat waste caused by excessively high exhaust temperatures, achieving a good balance between drying efficiency and energy consumption. The coordinated inlet and outlet temperatures ensure rapid drying of the slurry while shaping high-quality spherical granules with good flowability, high green strength, and suitability for subsequent high-pressure molding.
[0063] Meanwhile, the atomizer frequency is preferably between 120Hz and 150Hz. If the atomizer frequency is below 120Hz, the slurry will stick to the wall very badly; if the atomizer frequency is above 150Hz, it will result in too much fine powder, and the granulated particles will not meet the requirements. The best effect is achieved when the atomizer frequency is 120Hz.
[0064] The granulated particles obtained above are further sieved to separate the powder within the target particle size range. Then, a release agent is added in proportion and the mixture is homogenized by shaking in a shaking machine for a preset time to ensure that the release agent is mixed evenly, thus obtaining the mixed granulated material.
[0065] In this embodiment, the target particle size range of the powder obtained by granulation particle screening is 80 mesh to 250 mesh. This particle size range is the optimal particle size range for dry pressing molding process. The powder particles in this range are of moderate size, and the friction between particles is in a balanced state, resulting in excellent flowability and filling properties. During the subsequent pressing molding process, the powder can quickly and uniformly fill the mold cavity, avoiding bridging and voids caused by excessive fine powder, and ensuring the uniformity of the pressed density. At the same time, the particle size distribution of the powder in this range is relatively narrow, the gaps between particles are uniformly distributed, and the binder in the slurry is also more uniformly distributed. During the subsequent high-temperature sintering process, the powder can achieve synchronous and uniform volume shrinkage, effectively avoiding deformation, warping, or internal microcracks in the sintered body caused by local shrinkage differences, thereby significantly improving the dimensional accuracy and capacitance consistency of the high-voltage ceramic capacitor.
[0066] Meanwhile, calcium stearate is preferred as the release agent, and its addition amount is 0.1% to 0.4% of the powder mass. If the amount of calcium stearate added is too small, it will not achieve the lubrication effect, and if the amount added is too large, it will increase impurities. The effect is best when the amount of calcium stearate added is 0.1% of the powder mass.
[0067] The optimal time for homogenization is 40 min to 1 h. The best results are achieved when the processing time is 1 h.
[0068] Step 103: Press the granulated material into shape to obtain a blank with the target density.
[0069] In this step, the granulated material obtained above is pressed into blanks of the target density.
[0070] In this embodiment, the target density of the preform is 3.7 g / cm³ to 3.8 g / cm³. Within this density range, the powder particles can achieve effective rearrangement and plastic deformation within the mold, ensuring that the preform has sufficient mechanical strength to withstand subsequent handling and debinding processes. Simultaneously, controlling this density range helps regulate the volume shrinkage rate of the preform during subsequent high-temperature sintering, thereby ensuring the dimensional accuracy and structural integrity of the final sintered ceramic body.
[0071] Step 104: Perform a pre-firing process on the blank to obtain a pre-firing blank with de-adhesive.
[0072] In this step, the pre-fired blank after molding is subjected to debinding treatment to obtain a debinded blank.
[0073] In this embodiment, the preferred temperature for the pre-firing treatment is 600℃~700℃, with a holding time of 5h~10h. Within this temperature range, combined with a sufficient holding time of 5h~10h, the organic materials such as adhesives and release agents added in the previous stage have enough time to decompose into gases and be smoothly discharged. This effectively avoids fatal defects such as pores, microcracks, or delamination inside the ceramic due to excessively rapid volatilization or residue of organic materials. Simultaneously, the 600℃~700℃ temperature setting and the slow holding process of 5h~10h provide sufficient time buffer for the severe volume shrinkage of the blank during the adhesive removal process. This effectively avoids thermal stress concentration caused by excessively rapid heating or large local temperature differences, thereby significantly reducing the risk of warping, deformation, or cracking of the blank during the adhesive removal stage and improving the pass rate of the preceding process. The optimal temperature for the pre-firing treatment is 680℃, with a holding time of 8h.
[0074] Step 105: The debonded blank is subjected to high-temperature sintering treatment to obtain a sintered ceramic body.
[0075] In this step, the degummed blank obtained above is placed in a tunnel furnace for high-temperature sintering to obtain a sintered ceramic body.
[0076] In this embodiment, the preferred high-temperature sintering temperature is 1280℃~1380℃, the preferred total sintering time is 25h~30h, and the preferred holding time is 3h~5h. This sintering temperature is the optimal temperature for barium titanate-based dielectric materials to achieve sufficient solid-phase reaction and liquid-phase sintering, promoting material transport and eliminating porosity between powder particles, ultimately resulting in extremely high density of the ceramic body, thereby improving the withstand voltage of the high-voltage ceramic capacitor. The relatively long total sintering time of 25h~30h provides sufficient conditions for the rapid diffusion and uniform distribution of rare earth elements at the grain boundaries, ensuring that the grain center retains a high dielectric constant, while the grain edges are rich in modifiers to provide temperature stability, thus achieving excellent dielectric properties that meet the requirements of a wide temperature range. The holding time of 3h~5h, combined with the sintering temperature, can suppress abnormal grain growth and ensure that the grains maintain uniform size while reaching the ideal size.
[0077] Step 106: Perform post-processing and electrode encapsulation on the sintered ceramic body to produce the finished high-voltage ceramic capacitor.
[0078] In this step, the sintered ceramic body undergoes post-treatment processes such as surface grinding, ultrasonic cleaning, silvering, silver firing, electrode welding, and epoxy casting, as well as electrode encapsulation, to produce a finished high-voltage ceramic capacitor.
[0079] The high-voltage ceramic capacitor preparation method provided in this invention uses ball milling and high-speed sand milling to refine the powder, while segmented glue removal and long-term sintering eliminate the internal stress of pores. The capacitance decays slowly under long-term outdoor temperature difference and humidity conditions, and the capacitance will not permanently shift after a lightning strike. The equipment has a longer maintenance-free period, reducing operation and maintenance costs. By using fixed process parameters for ball milling, sand milling, granulation, and sintering, and uniformly screening particle size and adding release agent, the performance difference between the same batch and different batches of products can be minimized, resulting in a high yield rate. Existing production lines can be put into production directly with low modification costs.
[0080] The following specific embodiments further illustrate the method for preparing a high-voltage ceramic capacitor provided by the present invention.
[0081] Table 1
[0082]
[0083] Prepare the raw materials for Examples 1 and 2 according to the proportions in Table 1 above, and mix them evenly to obtain a mixed raw material. Add the mixed raw material, zirconium balls, deionized water, binder, dispersant and defoamer to a ball mill at a mass ratio of 1:3:1:0.1:0.01:0.01, and ball mill for 1 hour. Then, pass the mixture through a 200-mesh sieve to separate the primary slurry. Pour the primary slurry into a sand mill and sand mill it at a speed of 2100 r / min for 20 cycles to obtain a uniform media slurry.
[0084] The obtained slurry was placed in a centrifugal granulation tower for centrifugal spray granulation. The inlet temperature was 230℃, the outlet temperature was 110℃, and the atomizer frequency was 120Hz to obtain granulated particles. The granulated particles were passed through an 80-mesh sieve and a 250-mesh sieve to remove coarse material larger than 80 mesh and fine material smaller than 250 mesh. Then, calcium stearate was added, and the mixture was shaken in a shaker for 1 hour to finally obtain granules with a particle size of 80-250 mesh and a moisture content of 0.4%-0.6%.
[0085] The selected granules are pressed into cylindrical blanks with a density of 3.7 g / cm³, a thickness of 18.5 mm, and a sheet diameter of 42.5 mm.
[0086] The shaped blanks are placed in a debinding pre-firing furnace and pre-firing at 680℃ for 8 hours to obtain debinding blanks.
[0087] The debonded green body was placed in a tunnel furnace for sintering at 1280℃ for 25 hours, followed by a 4-hour holding period to obtain a sintered ceramic body. After sintering and shrinkage, the thickness of the sintered ceramic body was 15.72 mm and the diameter was 36.13 mm.
[0088] Finally, after the sintered ceramic body undergoes various processes such as surface grinding, ultrasonic cleaning, silver coating, silver firing, electrode welding, and epoxy casting, it is made into a finished high-voltage ceramic capacitor.
[0089] The performance of the high-voltage ceramic capacitors prepared in Examples 1 and 2 above was tested, and the results are as follows:
[0090]
[0091] The high-voltage ceramic capacitors prepared in Examples 1 and 2 were subjected to a 110kV lightning strike, and both passed 15 times in each direction.
[0092] In addition, temperature characteristic tests of the system were conducted within a temperature range of -40℃ to 70℃, and the results are as follows:
[0093]
[0094] The capacitance change rate of the high-voltage ceramic capacitors prepared in Examples 1 and 2 above is plotted as a function of temperature, as shown in the graph. Figure 2 As shown. From Figure 2 As can be seen, within the temperature range of -40℃ to 70℃, the capacitance change rate of the high-voltage ceramic capacitors prepared in Example 1 and Example 2 is within 0.2%.
[0095] This invention also provides a high-voltage ceramic capacitor, which is prepared using the high-voltage ceramic capacitor preparation method provided in the above embodiments. The detailed process will not be repeated here; please refer to the steps described in the foregoing embodiments.
[0096] In summary, the high-voltage ceramic capacitor dielectric material, high-voltage ceramic capacitor, and preparation method provided by the embodiments of the present invention overcome many defects of the prior art, bring significant technical advantages and practical value, and have the following beneficial effects:
[0097] (1) The dielectric constant can be adjusted from 120 to 180, which can be adapted to a variety of products and reduce R&D costs: The main phase of barium titanium is adopted, and the dielectric constant can be changed by adjusting the raw material ratio. Thus, a basic formula can be used to make capacitors of different specifications. There is no need to develop multiple systems separately, which reduces R&D and production investment. The capacitors are smaller and the equipment is easier to miniaturize.
[0098] (2) Good temperature stability from -40℃ to 70℃ and higher measurement accuracy: A variety of rare earth elements are used to stabilize the calcium zirconate lattice. Combined with fine grinding and long-term uniform sintering, the capacity change caused by temperature is reduced, so that the capacity change rate in the whole temperature range can be controlled within 0.2%. The partial pressure is stable under the temperature difference of outdoor seasons, the measurement error is small, and no additional temperature compensation accessories are required.
[0099] (3) Excellent high voltage partial discharge and withstand voltage performance, low heat generation and slow aging: Niobium is used to fill the lattice vacancies to reduce losses, bismuth element is used to lengthen the sintering to make the ceramic body dense and pore-free, and rare earth strengthens the grain boundary insulation, so that the finished product has no partial discharge above 33kV, no breakdown at 90kV withstand voltage, and passes all 110kV lightning impulse, and has less heat generation during high voltage operation, which delays dielectric aging and has a longer service life.
[0100] (4) Lead-free and environmentally friendly, while meeting high-voltage performance standards: Bismuth oxide and calcium zirconate are used to replace traditional lead components to improve the voltage resistance. The entire process is lead-free, so that the finished product meets environmental protection standards and solves the problem of insufficient voltage resistance of ordinary lead-free ceramics, making it suitable for the requirements of green power grid equipment.
[0101] (5) Resistant to damp heat, hot and cold cycles, and lightning strikes, with stable capacity over a long period of time: The process of refining powder by ball milling and high-speed sand milling is adopted. The glue is removed in sections and the long-term sintering eliminates the internal stress of the pores. Calcium zirconate strengthens the grain boundaries. As a result, the capacity of the finished product is slow to decay under long-term outdoor temperature difference and humid environment. The capacity will not be permanently shifted after lightning strikes. The equipment has a longer maintenance-free cycle and reduces operation and maintenance costs.
[0102] (6) Standardized process and good mass production consistency: The complete set of process parameters for ball milling, sand milling, granulation and sintering are fixed, the particle size is uniformly screened and the release agent is added, so the performance difference between the same batch and different batches of products is small, the production yield is high, the existing production line can be put into production directly, and the transformation cost is low.
[0103] In the above embodiments of the present invention, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions of other embodiments.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-voltage ceramic capacitor dielectric material, characterized in that, The material is made from the following raw materials by weight percentage: Barium carbonate 40%~45%, titanium dioxide 35%~40%, dysprosium trioxide 1.2%~3.0%, gadolinium trioxide 1.0%~2.8%, samarium trioxide 2.0%~4.2%, bismuth trioxide 3.5%~7.0%, niobium pentoxide 0.8%~2.2%, calcium zirconate 2.5%~5.5%.
2. A method for preparing a high-voltage ceramic capacitor, characterized in that, Includes the following steps: Barium carbonate, titanium dioxide, dysprosium trioxide, gadolinium trioxide, samarium trioxide, bismuth trioxide, niobium pentoxide, and calcium zirconate were mixed uniformly in a weight percentage ratio of 40%~45%: 35%~40%: 1.2%~3.0%: 1.0%~2.8%: 2.0%~4.2%: 3.5%~7.0%: 0.8%~2.2%: 2.5%~5.5% to obtain a mixed raw material. The mixed raw material was then added to grinding media, dispersion media, and dispersion aids and subjected to wet ball milling. After sieving, a primary slurry was obtained. The primary slurry was then subjected to sand milling dispersion treatment to obtain a uniform media slurry. The medium slurry is centrifuged and sprayed to obtain granulated particles; the granulated particles are sieved, and powder within the target particle size range is added to the powder, followed by mixing and homogenization to obtain the mixed granulated material. The granulated material is pressed into shape to obtain a blank of the target density; The blank is subjected to a pre-firing process to remove the glue, resulting in a pre-firing blank with the glue removed. The debonded green body is subjected to high-temperature sintering treatment to obtain a sintered ceramic body; The sintered ceramic body is post-processed and the electrodes are encapsulated to produce a high-voltage ceramic capacitor.
3. The preparation method according to claim 2, characterized in that, In the step of obtaining the primary slurry after sieving, the grinding medium is zirconium balls, the dispersion medium is deionized water, and the dispersion aid includes binders, dispersants, and defoamers. The mass ratio of the mixed raw materials, the grinding media, the dispersing media, the binder, the dispersant and the defoamer is 1:3:1:0.1:0.01:0.
01.
4. The preparation method according to claim 2, characterized in that, In the step of obtaining a uniform media slurry, the rotation speed of the sand mill dispersion treatment is 2100~2500 r / min, and the number of cycles is 15~25.
5. The preparation method according to claim 2, characterized in that, In the step of obtaining granulated particles, the process parameters of centrifugal spray granulation are: inlet temperature of 230℃~250℃, outlet temperature of 100℃~120℃, and atomizer frequency of 120Hz~150Hz.
6. The preparation method according to claim 2, characterized in that, In the step of obtaining the mixed granulated material, the target particle size range is 80 mesh to 250 mesh; In the step of obtaining the mixed granulated material, the release agent is calcium stearate, and its addition amount is 0.1% to 0.4% of the powder mass; the mixing and homogenization treatment time is 40 min to 1 h.
7. The preparation method according to claim 2, characterized in that, In the step of obtaining the blank with the target density, the target density of the blank is 3.7 g / cm³ to 3.8 g / cm³.
8. The preparation method according to claim 2, characterized in that, In the step of obtaining the debonded blank, the temperature of the debonded preheating treatment is 600℃~700℃, and the holding time is 5h~10h.
9. The preparation method according to claim 2, characterized in that, In the step of obtaining the sintered ceramic body, the high-temperature sintering temperature is 1280℃~1380℃, the total firing time is 25h~30h, and the holding time is 3h~5h.
10. A high-voltage ceramic capacitor, characterized in that, The high-voltage ceramic capacitor is prepared using the high-voltage ceramic capacitor preparation method described in claims 2 to 9.
Citation Information
Patent Citations
High dielectric NP0 ceramic dielectric material and preparation method thereof
CN121583773A